Analisis Pengaruh Harga Lokasi dan Kualitas Layanan terhadap Kepuasan Konsumen pada Coffee Shop Kopi Kenangan di Sidoarjo - Yusa Marzuki; Handy Aribowo (Tamilis Synex: Multidimensional Collaboration, 2024)
The title of this research is "The Influence of Price, Location, and Quality of Service on Consumer Satisfaction at the Kopi Kenangan coffee shop in Sidoarjo". This study aims to analyze the effect of price, location, and service quality on customer satisfaction. .As for the research method used is quantitative method. Data collection instrument using a questionnaire. The independent variables are price, location, and service quality and the dependent variable is customer satisfaction at the Kopi Kenangan coffee shop. All statements are valid, reliable and normal.the effect of price, location, and service quality on consumer satisfaction, based on the tests carried out, the results of this study show that with a coefficient value of 0.840 it can be seen that the price variable (X1) is 0.293, the location variable (X2) is 0.230, the service quality variable (X3) .of 0.312.Price (X1), Location (X2) and Service Quality (X3) which have a strong relationship to customer satisfaction can be seen in the R Square value of 0.704, which indicates that the independent variables consisting of the variables Price, Location and Service Quality can be explained with.Consumer satisfaction of 70.4% is able to explain the dependent variable, namely consumer satisfaction (Y), while the remaining 29.6% is influenced by other variables not examined in this study. .The conclusion of this study is that price, location, and service quality have a significant effect on customer satisfaction at the Kopi Kenangan coffee shop.